A Solar Timber-Dryer Equipped with an Air Collector - Jozef Víglasky; Nada Langova; Peter Horbaj (Communications - Scientific letters of the University of Zilina, 2006)
A generally well-known high energy requirement for technological processes of timber drying and the fact that the world’s supply of the conventional energy sources has considerably decreased are the decisive factors forcing us to look for some new, if possible, renewable energy sources for this process emphasising their environmental reliability.One of the possibilities of how to replace, at least partly, the conventional energy sources – heat in a drying process is solar energy.Air-drying of timber usually has a series of disadvantages such as time expenditure, drying defects in the wood and inadequate final moisture content. To avoid these drawbacks, kiln drying is used in many cases to dry the timber, but this involves higher investments for equipment and greater operating costs. The energy used to dry timber is approximately 60 to 70 % of the total energy used to manufacture timber.A method that obviates or reduces the disadvantages of air-drying and, at the same time, reduces the costs of kiln drying, is drying with solar heat. For the most part, fossil fuels are currently used to dry timber products. Solar energy can replace a large part of this depletable energy since solar energy can supply heat at the temperatures most often used to dry wood (i.e. from 40 to 100 °C). Solar timber-dryers offer an attractive solution.